Pesticide residues monitoring in underground drinking water, Neuquén province, northern Patagonia, Argentina - Sánchez, Victoria Guadalupe (2019)
Neuquén province is located in the west of Argentina, at the northern end of Patagonia. In this province, information regarding groundwater distribution and quality is very scarce, and the monitoring of water resources quality is not carried out periodically. It is well known that several pesticide families, such us organophosphates, carbamates and neonicotinoids, are applied in this region to maintain crop quality and production. Pesticide application by ground-based spraying equipment, the climatic conditions and the physical and chemical properties of these compounds, facilitate that a substantial fraction of the active ingredient may reach air, soil and water sources. The objective of this study was to evaluate the pesticide presence in groundwater, in order to provide information about the water quality for human consumption. Seventeen organophos-phate and four carbamate residues were monitored from 2014 to 2015 by gas chromatography with a nitrogen-phosphorus detector, in groundwater samples collected from depth wells, located in rural areas corresponding to Senillosa, Plottier, Vista Alegre and Centenario cities, in Neuquén province. These cities are intensive agricultural areas, which supply the North Patagonia region with fresh fruits and vegetables, and where groundwater is utilized for human consumption. In this study, organophosphate and carbamate concentrations were below 0.020 and 0.030 μg/L, respectively, and lower than the accepted limits established by the Guidelines for Canadian drinking water quality (2017) and the Guidelines for drinking water quality (2011) of the World Health Organization for these pesticides.